STRATEGI PEMBINAAN KARAKTER KOMUNIKATIF PESERTA DIDIK DI SDN CIBADAK 1 - Teti Nurbaeti (Jurnal PGSD, 2022)
Many of us do not realize that the moment together with students is very important. Sometimes we are not sensitive to students' moments of togetherness when they have snacks or meals. Seeing this, the researcher felt the need to create a family atmosphere in the classroom. The objectives of this research include developing and increasing a sense of solidarity among students in the school environment, especially in the classroom. And to create new good habits for friendly relations among students. Researchers used descriptive research methods. Here the researcher describes what the researcher finds in the field when the researcher conducts the research and this description is based on the facts that exist in the school. No more children sitting alone and feeling like they don't have friends in class. After they finished eating, the children worked together to clean up the garbage around them. Do not be indifferent to the interaction between fellow students in class. Everything can go well, including friendly characters that initially are not good can turn out to be good, if there is effort and done seriously without giving up, because when children interact with each other they are able to find happiness in school and this happiness can make them excited to come and study at school, they can motivate each other and create brilliant achievements in their respective fields, friendships that are created well make children feel the beauty of school. Keywords: Friendship, Communicative Character, Learners.